1990
DOI: 10.1177/089686089001000404
|View full text |Cite
|
Sign up to set email alerts
|

The Management of Hydrothorax in Continuous Ambulatory Peritoneal Dialysis (CAPD)

Abstract: Four patients on continuous ambulatory peritoneal dialysis (CAPD) developed large, symptomatic pleural effusions after commencing peritoneal dialysis. Pleuroperitoneal fistula in each case was diagnosed by the presence of a high glucose content in pleural fluid, with a normal corresponding blood sugar, and was confirmed by isotope or contrast peritoneography. Two patients had their effusions drained percutaneously, and then underwent pleural sclerosis with intracavitary tetracycline. Two patients had a thoraco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…The conventional pleurodesis procedure involves administration of a chemical agent via an intercostal chest drain (thoracostomy tube), followed by designated (recumbent) positioning of the patient every 10-15 minutes to allow adequate distribution of the agent. The agents of choice include talc (15,40), tetracycline (14,(16)(17)(18)(19)21,22,41), autologous blood (5,17,42,43), fibrin glue (44,45), and hemolytic streptococcal preparation OK-432 (17). There are currently insufficient data to suggest a superior efficacy of any one over the other.…”
Section: Conventional Pleurodesismentioning
confidence: 99%
“…The conventional pleurodesis procedure involves administration of a chemical agent via an intercostal chest drain (thoracostomy tube), followed by designated (recumbent) positioning of the patient every 10-15 minutes to allow adequate distribution of the agent. The agents of choice include talc (15,40), tetracycline (14,(16)(17)(18)(19)21,22,41), autologous blood (5,17,42,43), fibrin glue (44,45), and hemolytic streptococcal preparation OK-432 (17). There are currently insufficient data to suggest a superior efficacy of any one over the other.…”
Section: Conventional Pleurodesismentioning
confidence: 99%
“…These scans have sensitivity rates ranging between 40% and 50%, but they still have a limited utility in locating the site of the fistula. 7 The diagnosis of PDrelated hydrothorax in our patient was clear-cut based on the recurring nature of the effusion and the results of biochemical tests. Consequently, we proceeded with thoracoscopy.…”
Section: Discussionmentioning
confidence: 72%
“…Success rates of up to 60% have been reported, with patients being able to resume maintenance PD. 7,8 In cases where PD cannot be reinstituted, the patient should be permanently switched to chronic hemodialysis. Different management strategies have been suggested to treat peritoneal-pleural leakages and resume PD.…”
Section: Discussionmentioning
confidence: 99%
“…The first descriptions of this complication are credited to Edward, Unger, Finn, and Jowett in the 1960s (13,14). Since then, others have reported such cases and examined different aspects of this complication (15)(16)(17)(18)(19)(20)(21)(22)(23). The prevalence of this complication varies, ranging from 1.6% in Nomoto et al's series, which reported 50 cases of hydrothorax in a population of 3195 PD patients (17); 2.9% in the series studied by Shemin et al (18); and as high as 10% in Chow et al's series (19).…”
mentioning
confidence: 99%
“…On many occasions, it forces the patient to withdraw from PD and to accept a temporary or permanent transfer to hemodialysis (HD) (11-23). It has been described much more often in women (13)(14)(15)(16)22), although only 46% of Nomoto's patients were women. It develops chiefly in the right hemithorax, indeed 88% of Nomoto's cases were in this location (17).…”
mentioning
confidence: 99%